2019
DOI: 10.1503/cjs.001018
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis for pain in orthopedics: a systematic review focusing on study methodology

Abstract: Background: Medical cannabis use is an emerging topic of interest in orthopedics. Although there is a large amount of literature on medical cannabis use for managing various types of pain, few studies have focused on orthopedic conditions. There is little high-quality evidence in core orthopedic areas. The objective of this study was to summarize the literature on the efficacy of cannabis use for pain related to orthopedic conditions. Methods: We conducted a systematic review of the literature on the use of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“… 4 Active research explores the therapeutic benefits of cannabinoids in orthopaedics, particularly for back pain, hip and knee arthritis, trauma-related pain, and postsurgical pain. 5 , 6 …”
mentioning
confidence: 99%
“… 4 Active research explores the therapeutic benefits of cannabinoids in orthopaedics, particularly for back pain, hip and knee arthritis, trauma-related pain, and postsurgical pain. 5 , 6 …”
mentioning
confidence: 99%
“…The therapeutic application of cannabinoids is an emerging area of research. While Madden et al focused on study methodology in their reviews appraising the literature through 2017 [8,29], new studies have since been published [9,18,24,27]. In addition to evaluating these new studies, we sought to narrow the focus of our review to analgesic and opioid-sparing effects of cannabinoids within orthopedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The use of cannabinoids has been investigated in other applications including chronic pain, appetite stimulation, glaucoma, and anxiety [7]. The effects of these compounds have been studied to a lesser extent in orthopedic surgery [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Regarding the effect of CBD on pain, there are no published investigational trials on the effects of CBD alone on musculoskeletal pain, but there is low-quality evidence supporting the efficacy of THC-predominant compounds in reducing pain. 14,[23][24][25][26][27] A recent systematic review on this subject found many low-quality observational or noncontrolled studies but only 5 randomized controlled trials, only 1 of which showed a low risk of bias. 25 The trials consisted of heterogeneous patient populations, orally administered, THCbased compounds, and follow-up periods ranging from 300 minutes to 14 weeks.…”
Section: Discussionmentioning
confidence: 99%